Foreign Language Learning as Cognitive Training to Prevent Old Age Disorders? Protocol of a Randomized Controlled Trial of Language Training vs. Musical Training and Social Interaction in Elderly With Subjective Cognitive Decline - Nijmeijer, Saskia E.; van Tol, Marie-José; Aleman, André; Keijzer, Merel (Frontiers in Aging Neuroscience, 2021)
Introduction: With aging comes a reduction of cognitive flexibility, which has been related to the development of late-life depression and progression of general cognitive decline. Several factors have been linked to attenuating such decline in cognitive flexibility, such as education, physical exercise and stimulating leisure activities. Speaking two or more languages has recently received abundant attention as another factor that may build up cognitive reserve, thereby limiting the functional implications of compromised cognition that accompany old age. With the number of older adults reaching record levels, it is important to attenuate the development of old-age disorders. Learning to speak a foreign language might offer a powerful tool in promoting healthy aging, but up to date effect studies are sparse. Here, the protocol that forms the foundation of the current study is presented. The present study aims to 1) examine the effects of a foreign language training on cognitive flexibility and its neural underpinnings, and on mental health, and 2) assess the unique role of foreign language training versus other cognitive or social programs. Method: 198 Dutch elderly reporting subjective cognitive decline are included and randomized to either a language intervention, a music intervention, or a social control intervention. During three to six months, the language group learns English, the music group learns to play the guitar and the social group participates in social meetings where art workshops are offered. At baseline, at a three-month follow-up, and at six months after termination of the training program, clinical, cognitive and brain activity measurements (combined EEG and fNIRS methods) are taken to assess cognitive flexibility and mental health. Discussion: This is the first trial addressing combined effects of language learning in elderly on cognition, language proficiency, socio-affective measures, and brain activity in the context of a randomized controlled trial. If successful, this study can provide insights into how foreign language training can contribute to more cognitively and mentally healthy years in older adulthood. The trial is registered at the Netherlands Trial Register, July 2 2018, trial number NL7137 (https://www.trialregister.nl/trial/7137).